2018
DOI: 10.26832/24566632.2018.030103
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mulching on Growth and Yield Components of Selected Varieties of Wheat (Triticum Aestivum L.) under Field Condition

Abstract: Wheat is facing increased high temperature during its grain filling period in Bangladesh which reduces yield drastically. Mulching may help to mitigate this problem. Therefore, a field experiment was carried out at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh during the period from November 2015 to March 2016 to find out growth and yield performance of wheat as influenced by mulching. The experiment comprised of two factors viz., variety and mulching. The variety comprised of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…Conversely, traditional tillage experiments exhibited the lowest dry matter yield, possibly due to subsurface soil compaction hindering plant growth and reducing dry matter production. These results were consistent with similar research by Akter et al [19], further emphasizing the importance of tillage practices in influencing dry matter accumulation. Building upon these findings, Alam et al [20] underscored the significance of dry matter accumulation as a key determinant of photosynthetic efficiency and plant growth.…”
Section: Role Of Mechanization In Rice Wheat Cropping Systemsupporting
confidence: 93%
“…Conversely, traditional tillage experiments exhibited the lowest dry matter yield, possibly due to subsurface soil compaction hindering plant growth and reducing dry matter production. These results were consistent with similar research by Akter et al [19], further emphasizing the importance of tillage practices in influencing dry matter accumulation. Building upon these findings, Alam et al [20] underscored the significance of dry matter accumulation as a key determinant of photosynthetic efficiency and plant growth.…”
Section: Role Of Mechanization In Rice Wheat Cropping Systemsupporting
confidence: 93%
“…The early maturity of such cultivar may be caused a decrease in flag leaf area and total chlorophyll. In this concern, other investigators found variation among some wheat varieties in their plant height (Mekkei & El Haggan, 2014;Abdelkhalek et al, 2015 andAwad et al, 2015), flag leaf area (Zaki et al, 2007), chlorophyll (Kilic &Yagbasanlar, 2010 andAkter et al, 2018) and no. of days to heading and to maturity (Abd El-Rahman & El-Saidy, 2016, El Hag, 2017 and El Hag & Shahein, 2017).…”
Section: Resultsmentioning
confidence: 92%